Evaluation Model of Learning in the Costa Rican Educational System: Perceptions of Teachers of I and II Cycles of Basic General Education - Pawlowski, Josiane (2025)
Objective. To evaluate the perceptions of teachers from the 1st and 2nd cycles of Basic General Education in the year 2023 regarding the assessment model proposed by the Ministry of Public Education of Costa Rica. Methodology. A concurrent mixed-methods design was used. The study included 294 teachers (92.2% women), with ages ranging from 22 to 68 years. An online survey was administered via the LimeSurvey platform, including both closed- and open-ended questions. The invitation was sent through institutional email. Analysis of Results. Closed-ended questions were analyzed using SPSS statistical software, while open-ended responses were coded and thematically categorized. Results. Teachers expressed agreement with the guidelines for evaluating homework, attendance, and the development of written tests based on learning indicators. However, they reported difficulties in understanding and applying the guidelines related to the “daily work” component. Conclusions. Recommendations to improve the current model include: (1) reviewing the categories and percentage weights assigned to each assessment component, (2) clarifying the structure and implementation of the daily work component, and (3) promoting more comprehensive learning-centered evaluation approaches.